Pengaruh Motivasi Kerja, Kedisiplinan Kerja dan Lingkungan Kerja Terhadap Kinerja Guru SMP Kabupaten Kulon Progo - Fatmaningrum, Sakti Riana; Supriyoko, Supriyoko (Media Manajemen Pendidikan, 2024)
This study aims to examine and analyze (1) the effect of work motivation, work discipline, and work environment together on teacher performance, (2) the effect of work motivation on teacher performance, (3) the effect of work discipline on teacher performance, (4) ) the influence of the work environment on teacher performance. This type of research uses a quantitative approach method. The population of this study were 160 private junior high school teachers in Kapaenwon Wates, Kulon Progo Regency. Data collection techniques using questionnaires. used is a questionnaire. Data analysis techniques for major hypotheses using multiple linear regression analysis and minor hypotheses with partial correlation. The results of this study indicate that: (1) There is a positive and significant influence together of work motivation, work discipline, and work environment on teacher performance, (2) There is a positive and significant influence of work motivation on teacher performance, (3) There is a positive and significant influence of work discipline on teacher performance, and (4) There is a positive and significant influence of work environment on teacher performance. Of the three independent variables, the dominant influence on teacher performance is work motivation.